Castor Plant Project / Mohammad Zakwan Hakim Bahazan ... [et al.] - Bahazan, Mohammad Zakwan Hakim; Nasir, Mohd Haliff; Kinsiu, Mellisa; Joblis, Norshidah (2010)
Recently, the world is facing a problem regarding the production of fuels. The price of today's fuels increasing from day to day. This is because the sources of fuels is decreasing due to high demand from the consumers. There are many ways that have been taken by the government of around the world to solve this problem. The government of Malaysia has found a way which is using the palm oil as a replace or reduces the uses of fuels. Therefore, we are from Castro Company introducing a new way that can help to solve the fuels problem. We introduce the plant can replace the biodiesel and biofuel which is called castor oil plant and in the scientific name is Ricinus Comrnunis. This plant can produces fuels or oil from the seed. The seed contain 40% - 60% oil more than palm oil that only provides 20% of fuels. This plant also has a high potential to generate more revenue and become a renewable of fuels. Castor plant can easy to grow in any kind of soil and very suitable planted in the weather and climate our country. Castor plant is not only use as a renewable of fuels, but this plant also have its many function such paint, soap, hair treatment, ink. Our location that we have chosen to plant this plant is at keningau, sabah and the land is contributed by the partner in our company. The reason we choose this area is because this area have a good soil and suitable to this plant which can grow and produces a good quality of castor seeds. We are as a supplier of a castor plant seed introduce the profitable business and the plant that will become the important plant in oil industry.